Trace element composition of snow cover components in the city of Chita and its environs - Evgeniy A. Bondarevich (RUDN Journal of Ecology and Life Safety)
The variation in the concentrations of chemical elements of snow cover in melt water and native dust in the urbanized area of Chita and its environs was studied in comparison with the background area and literature data from other regions of Russia and Mongolia. The study of the accumulation of compounds of chemical elements in the components of snow cover makes it possible to assess the degree of pollution of the surface layer of the atmosphere under technogenesis conditions and to identify key sources of pollution. The goal of the work was to compare the amounts of a number of microelements in melted snow water and in native dust residue in areas of different degrees of technogenic load. The materials were dust and snow meltwater, in which the quantitative content of 22 chemical elements was determined using the X-ray fluorescence method of total external reflection on an S2 Picofox spectrometer (Bruker Nano GmbH, Germany). A low content of ionic forms of elements in the aqueous phase of snow was revealed, with an excess of the maximum permissible concentration for Mn by 1.5-2 times under technogenesis conditions. The concentrations of water-soluble forms of trace elements were comparable to data from other regions. The dust fraction of snow, on the contrary, was characterized by significant contamination with sparingly soluble forms of chemical elements, while no excess of the maximum permissible concentration / approximately permissible concentration was noted, and in comparison with the clarke for soils of populated areas, a slight excess of the content of As, Sn and W was noted. The dust fraction of the Chita snow cover, compared to the background, is enriched in Th, Rb, Cr and Ga; in the Chita region, intensive accumulation of Cr, As and Sr in the dust was revealed. Significantly larger amounts of microelements compared to Transbaikal samples were detected for the cities of Ulaanbaatar, Blagoveshchensk, and in somewhat smaller quantities Tyumen and Tobolsk. The mass fraction of water-soluble forms for most microelements was significantly less than 0.1%, while a tendency was revealed to increase the number of ionic forms of elements from the urbanized area to the background areas.